PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR KETERAMPILAN SISWA KELAS VIII I SMPN 28 PADANG - NURLELY, Drs. Erwin, M.Sn, Drs. Wisdiarman, M.Pd (Universitas Negeri Padang, 2014)
This article is based on research results (PTK) on the eighthgrade students of SMP 28-1 in Padang, that the problems in thesubjects embroidery skills. The results of those who have not learnedthe skills to meet the specified minimum learning ketuntatasan schoolthat approached 80 the Problems with the application of creative nonproductive learning strategies.The results of the study, showed significantly improved learningoccurs embroidery skills class VIII-1 SMP 28 Padang. An increase inthe average learning outcomes are significant. It is recommended toteachers of art or a field of study that is cognate to implement thisstrategy in improving student learning outcomes.Keywords: application of creative-productive strategy, increaselearning outcomes.